PENGARUH AKUNTASI FORENSIK, WHISTLEBLOWING SYSTEM, DAN AUDIT INVESTIGASI TERHADAP PENGUNGKAPAN FRAUD DENGAN SKEPTISISME PROFESIONAL SEBAGAI VARIABEL MODERASI - Ningsih, Indah Ramada; Novietta, Liza; Nurmadi, Ruswan (UNIVERSITAS DHARMAWANGSA, 2025)
Fraud disclosure is a crucial issue in public sector accountability that requires effective mechanisms to detect and prevent fraudulent practices. This study aims to examine the impact of forensic accounting, whistleblowing systems, and investigative audits on fraud disclosure, and to test the role of professional skepticism as a moderating variable. Using a quantitative approach with an associative research design, the population comprised all 183 employees of the Financial and Development Supervisory Agency (BPKP) of North Sumatra Province. Through a saturated sampling method, 76 valid responses were collected using questionnaires. Data were analyzed with multiple linear regression and moderated regression analysis (MRA). The results show that forensic accounting, whistleblowing systems, and investigative audits have a positive and significant effect on fraud disclosure. However, professional skepticism does not moderate the relationship between these variables and fraud disclosure. These findings suggest that the application of forensic accounting, whistleblowing mechanisms, and investigative auditing can strengthen fraud disclosure practices, but auditors’ professional skepticism does not significantly enhance this relationship. This study contributes to the existing literature by underlining the limitations of professional skepticism as a moderating factor in fraud disclosure, particularly within public sector audit institutions in Indonesia